Plant breeding for organic agriculture: something new? - Crespo‑Herrera, Leonardo A.; Ortiz, Rodomiro (BioMed Central, 2015)
The role of both organic (OF) and conventional (CF) farming remains open to debate particularly when related to food security and climate change. Targeting plant breeding for OF can contribute to reduce its yield gaps vis-à-vis CF. Currently, the cultivars produced for CF are also used in OF, however, it is unreasonable that all lines bred for CF will always perform well in OF. Nonetheless, plant breeding goals for OF and CF converge at aiming for high productivity, host plant resistance or tolerance to biotic and abiotic factors, and high resource-use efficiency. Likewise end-use quality and local adaptation may be more important for OF as the resource recycling and quality of the inputs that are used vary from region to region, even though OF practices are highly regulated. This article provides an overview on organic plant breeding (OPB) with a perspective from conventional plant breeding, highlights the main traits, their source of variation, and what methods and tools are available for their breeding. It concludes listing some organic crop breeding achievements and providing an outlook on what needs to be done for OPB.
DOI 10.1186/s40066-015-0045-1
Keywords: Conventional agriculture; Conventional breeding; Organic agriculture; Organic plant breeding